The evaluation of the epistemological views of secondary education pre-service teachers - Akpinar, Burhan; Ozdas, Faysal; Yildirim, Bilal; Karahan, Osman (Elsevier Science Bv, 2013)
The aim of this study is to determine the epistemological views of secondary education pre-service teachers and to evaluate those views. The data used in the study, which was carried out using survey model, was obtained through a questionnaire applied to 420 pre-service teachers studying pedagogical formation at Firat University. The data were analyzed using descriptive statistics techniques. In the study, it was discovered that teacher candidates had views similar to those defended by quantum and post-modern paradigm regarding the three basic dimensions of epistemological belief: source, certainty, and simplicity of knowledge. As for the dimension of the source of information, it was observed that male teacher candidates and Mathematics Department teacher candidates had more positivist views compared to others. Regarding the dimension of complexity of knowledge, female teacher candidates were closer to positivism, and as for the certainty of knowledge, teacher candidates from the departments of physics, chemistry and biology had views closer to quantum and post-modern epistemology. (C) 2013 The Authors. Published by Elsevier Ltd.
3rd World Conference on Learning, Teaching and Educational Leadership (WCLTA) -- OCT 25-28, 2012 -- Brussels, BELGIUM
Keywords: Epistemology; pre-service teachers; curricular epistemology